Annealing effects on magnetic properties and strength of organic-silicon epoxy resin-coated soft magnetic composites. (August 2014) - Xiao, Ling; Sun, Yanhua; Ding, Chunhua; Yang, Lihua; Yu, Lie
Soft magnetic composites (SMCs) can be described as soft magnetic powders covered by electrically insulating layers. In this work, iron powders with high purity and organic-silicon epoxy resin were chosen for good magnetic properties, thermal stability, and mechanical properties, respectively. The effect of amount of resin, different annealing temperatures on the microstructure, and performance of SMCs was investigated. Results show that organic-silicon epoxy resin has excellent properties as dielectric coating materials for coating iron powders and maximum heat-resistant temperature is about 400 ℃. According to magnetic properties and flexural strength analysis, the optimum annealing temperature of organic-silicon epoxy resin-coated composite is 200 ℃. Furthermore, the finite element analysis indicates that the strength of the whole composites is related to the adhesion of resin and iron and the strength of resin itself.